Real Exchange Rate Behavior and Economic Growth : Evidence from Egypt, Jordan, Morocco, and Tunisia - Shabsigh, Ghiath (IMF Working Papers; Working Paper ;, 1999)
This paper examines the effect of the real exchange rate misalignment (RERMIS) on the collective economic growth of Egypt, Jordan, Morocco, and Tunisia. The paper constructs three measures of exchange rate misalignment based on purchasing power parity; a black market exchange rate; and a structured model. The empirical investigation confirmed the adverse effect of RERMIS on growth, using all measures of RERMIS, as predicted by endogenous growth models. The results also highlighted the role of other factors; specifically, capital growth and population have the theoretical signs predicted by the Solow growth model and are statistically significant.